Piero Manzoni : catalogo generale - Celant, Germano (Milano : Prearo Editore Milano, 1989)
In 1960 he invited the public to "consume" art, eating hundreds of eggs that had been signed with his thumbprint, and from 1961, simultaneously with Beuys, Ben, Rauschenberg and Klein, he became interested in the artistic and aesthetic reality of the body. Thus he considered as works of art faeces, blood and breath and signed, as living sculptures, the bodies of live people. In parallel to these artistic recognitions of corporeal material he built up the magical, parallelepiped bases on which any person or object could be placed, and for all the time they remain on these bases they are considered as works of art. The largest base was constructed at Herning, in Denmark, known as the "Base of the World", an iron parallelepiped which, being overturned, "replaces" the world, which in this way becomes an enormous living sculpture.
The work of Piero Manzoni can be placed historically between the late fifties and the early sixties, thus coinciding at international level with the final years of American action painting and the European informalism, and the beginning of the neo-dada movement, fluxus and minimal art. If we study the career of Manzoni we can see how his work originally reflected the essential angst of such artists as Burri, Kline and Fautrier, entering the neo-dadaist climate from 1958 onwards with the production of "achromes" (works without colour), lines and alphabets. In his achromes Manzoni made a clean sweep of all image and personal mystique, while the lines are the constant materialistic affirmation of an infinite dimension reaching, at their longest, 7200 metres.
bibliog. p. 274-277
biog. p. 271-273
Engels en Italiaans
boek
Keywords: Manzoni, Piero